Rebecca and the movies - Greene, Jacqueline Dembar (American Girl Pub., 2009)
Rebecca Rubin worries that her tenth birthday will be ruined because it falls during Passover, but her mother's cousin Max, an actor, takes her with him to a movie studio, where she makes friends with an actress and a set carpenter.